Model Proyeksi Dan Optimalisasi Cash Flow Multi Proyek - Resela Irpiena; Ratna Setyawardani Alifen; Herry Pintardi Chandra (Program Studi Magister Teknik Sipil - Petra Christian University, 2016)
This study aims to create an integrated system that has the ability to project the schedule and cash flow of a multi project situation for construction companies, while optimizing them so that a more efficient schedule and financial planning is achieved. In this study, an efficient construction planning refers to a schedule combination that generates a cash flow with minimum overdraft for the company.This study focuses on utilizing floats from non-critical activities in initial or as-planned schedule. Iteration on the floats is done with evolutionary algorithm optimization method using projects’ durations and credit limit as constraints. The result is a combination of multi project schedules which generates the least amount of overdraft throughout the fiscal year to achieve minimum loans of thecompany.